Identification of the Utilization of Sports Facilities and Infrastructure in The Alak District's State Middle Schools - Ly, Revanto Mira; Ladjar, Maria Andriani Barek; Siagian, Fera Ratna Dewi; Tajuddin, Al Ihzan; Susanto, Ratno (JUMORA: Jurnal Moderasi Olahraga, 2024)
The infrastructure and facilities of schools have a significant impact on the educational process. The learning process would be hampered by inadequate infrastructure and amenities. claimed that as educational infrastructure and facilities are among the most crucial resources for assisting with the educational process in schools, it is vital to enhance their use and administration in order to meet the desired outcomes. The researcher employed observation, interviews, and documentation as part of a qualitative research methodology with a descriptive study strategy. Determining the condition of the infrastructure and physical education facilities possessed by each of the five schools is the goal of this study. A total of five research samples were gathered, with one sample being used in each school. Following observation, the data was recorded to serve as supporting evidence for this study. The findings of this study demonstrate that the PJOK infrastructure and facilities in junior high schools in the Alak sub-district fall into the following categories: SMP Negeri 6 Kupang's UPTD is classified as quite adequate, SMP Negeri 14 Kupang's UPTD is classified as quite adequate, SMP Negeri 15 Kupang's UPTD is classified as inadequate, SMP Negeri 17 Kupang's UPTD is classified as less feasible, and UPTD SMP Negeri 19 Kupang is classified as quite adequate